Stereoselective synthesis of (Z)-3-ylidenephthalides via AlCl3-mediated cyclization with 2-acylbenzoic acids. Issue 14 (2nd April 2020) - Wang, Xujie; Li, Gangsheng; Zhang, Xu; Feng, Ziming; Jiang, Jianshuang; Yang, Yanan; Zhang, Peicheng
Graphical abstract: Highlights: AlCl3 -mediated synthesis of ( Z )-3-ylidenephthalides is developed. Different 2-acylbenzoic acids are well performed in a moderate to high yield. The protocol is economical and the high Z/E selectivity is achieved. A possible AlCl3 -mediated elimination mechanism is proposed. This method is applicable for gram-scale preparation of ( Z )-3-ylidenephthalides. Abstract: An efficient method for the synthesis of ( Z )-3-ylidenephthalides is reported in moderate to high yield with AlCl3 as catalyst. Different substrates of the 2-acylbenzoic acids are well performed in the Z/E selectivity. This method is highlighted by the gram-scale synthesis of the natural product ( Z )-3-butylidene-5-hydroxyphthalide with anti-inflammatory activity.